Intracardiac rhabdomyoma in a newborn with tuberous sclerosis - I Kadek Suarca; Ida Bagus Agung Winaya; I Komang Kari (Indonesian Pediatric Society Publishing House, 2016)
Primary congenital cardiac tumors, especially intracardiac tumors, are rare in children. Rhabdomyoma is the most common one and usually diagnosed in the first few days of life. Referral from pediatric cardiac centers found that the incidence of cardiac tumors was 0.08%-0.20%. Rhabdomyoma represents 36%-42% in autopsy series and 79% in clinical series.